2003
DOI: 10.1196/annals.1288.041
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Diabetes‐Related Autoantibodies below Cutoff for “Positivity” in Young Nondiabetic Children

Abstract: The aim was to study the natural course of diabetes-related autoantibodies at low concentrations, below "positivity", in a nondiabetic population followed up from infancy. Blood samples were taken from 205 children at 6 weeks, 6 months, 18 months, and 5 years of age. Autoantibodies against GAD(65) (GADA), tyrosine phosphatase (IA-2A), and insulin (IAA) were determined by radioligand-binding assays. All children had detectable levels of GADA and approximately half had IA-2A, but only approximately 10% had detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It has been shown that the levels and reactivity profiles of NAAbs are prone to alterations in human disease, both autoimmune and nonautoimmune [24]. On the other hand, AAbs associated with autoimmune disease have been also demonstrated at low levels in healthy subjects [25]. In this study, despite the high overall frequency of serum ␣-INX AAbs, variable AAb levels were detected in individual sera, and even more, IgM ␣-INX AAb levels were increased in patients with idiopathic hypopituitarism.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that the levels and reactivity profiles of NAAbs are prone to alterations in human disease, both autoimmune and nonautoimmune [24]. On the other hand, AAbs associated with autoimmune disease have been also demonstrated at low levels in healthy subjects [25]. In this study, despite the high overall frequency of serum ␣-INX AAbs, variable AAb levels were detected in individual sera, and even more, IgM ␣-INX AAb levels were increased in patients with idiopathic hypopituitarism.…”
Section: Discussionmentioning
confidence: 96%
“…GAD 65 (GADA) and IA‐2 (IA‐2A) autoantibody titers were determined from serum samples using an immunoprecipitaton assay (35), and insulin autoantibodies (IAA) were measured using a radioimmunoassay described in detail elsewhere (36).…”
Section: Methodsmentioning
confidence: 99%